2012
DOI: 10.1186/1756-0500-5-113
|View full text |Cite
|
Sign up to set email alerts
|

Replacing paper data collection forms with electronic data entry in the field: findings from a study of community-acquired bloodstream infections in Pemba, Zanzibar

Abstract: BackgroundEntering data on case report forms and subsequently digitizing them in electronic media is the traditional way to maintain a record keeping system in field studies. Direct data entry using an electronic device avoids this two-step process. It is gaining in popularity and has replaced the paper-based data entry system in many studies. We report our experiences with paper- and PDA-based data collection during a fever surveillance study in Pemba Island, Zanzibar, Tanzania.MethodsData were collected on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
90
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 10 publications
10
90
4
Order By: Relevance
“…Using EDC reduced the time needed before and after data collection, as printing and data entry were largely eliminated; the latter reflected in the reduction in the average number of days from data collection to availability to scientists. Other evaluations have found that the overall time required was always shorter with EDC [3,6,7,13,19], despite additional time needed at the beginning for making tablet forms [5,15], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Using EDC reduced the time needed before and after data collection, as printing and data entry were largely eliminated; the latter reflected in the reduction in the average number of days from data collection to availability to scientists. Other evaluations have found that the overall time required was always shorter with EDC [3,6,7,13,19], despite additional time needed at the beginning for making tablet forms [5,15], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Our quantitative results on data quality are consistent with findings from other evaluations [3,6,7,10,11,1519]. On paper forms, the level of missing data increased with the complexity of skip patterns, while almost the opposite pattern was seen in EDC, showing the usefulness of programmed automatic skip patterns in guiding interviewers to the correct questions.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations